Nonlinear swing dynamics of tower crane load subject to stochastic wind excitation: A CFD/CSD coupling approach - Yu Sun; Xinhui Zhang; Peijin Liu; Qi Bian (PLoS ONE, 2026)
With the expanding deployment of tower cranes in high-altitude environments, the dynamic interference of stochastic wind excitation on load swing has become a critical concern. Conventional crane dynamic models, limited by assumptions of constant wind excitation and fully rigid crane structures, inadequately capture the multi-physics coupling effects among stochastic wind, flexible tower jib, and load swing, resulting in unreliable swing predictions under wind disturbances. To overcome these limitations, this study innovatively establishes a two-way fluid-structure coupling framework integrating tower crane multi-body dynamic model and full-direction wind field model to simulate wind-induced load swing during crane operations. Based on this framework, this study quantitatively reveals load swing behavior during luffing/slewing operations under stochastic wind excitation by clarifying the wind-structure-load coupling mechanism, specifically incorporating effects of time-varying windward pressure and tower jib wind-induced vibration. The results demonstrate that the time-varying windward pressure distribution(the error exceeds 10%) and tower jib wind-induced vibration significantly influence load swing(the maximum offset is 1.82°). Wind speed/direction variations induce obvious behavior deviations in load swing during crane operations, and there is a significant correlation between the changing trend in radial/tangential swing angles of the load under different wind directions. Using two-way fluid-structure coupling, this study quantifies the nonlinear swing behavior of tower crane load subjected to stochastic winds. The revealed mechanisms provide a quantitative basis for developing environment-adaptive anti-swing controllers and high-precision positioning systems in intelligent tower cranes.